Digital marketing and user-generated content: a case study of Vidago Palace Hotel - Clara, Irina (2022)
Digital marketing is essential for hotels. It is important to have a social media strategy and, simultaneously, to be aware of the guests’ opinions and reviews, be conscious of their satisfaction. In this sense, the content, and interactions of the different social media of Vidago Palace Hotel were analysed, and some suggestions for improvement were given. On the other hand, the hotel reviews in the main online review platforms were analysed, to understand the level of guest satisfaction. The results show that there should be more care at the social media strategy level, posting with more frequency.However, the reviews are excellent, which shows that the quality of service provided by the hotel. The exploratory nature of the study is one of its limitations, added by the fact that is based on a specific date that analysed its last 10 publications.